Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Kabupaten Karanganyar Tahun 1999-2014 - Adyanti, Titi Aminah, Dr. Daryono Soebagyo.,MEc (2017)
Economic growth is a problem in the long-term economy and is influenced by various factors. This study was conducted to analyze the effect of government spending, inflation, and labor to economic growth Karanganyar district. In this study using multiple linear regression analysis model of ordinary least squares (OLS). For purposes of analysis used secondary data (time series) with a vulnerable period covering 1999 to 2014 GRDP data Karanganyar district, government expenditure data, the inflation data and employment data. The data obtained from the Central Statistics Agency (BPS) Karanganyar district, sources and other relevant sources.